Perlindungan Hukum terhadap Konsumen Akibat Kerugian yang Ditimbulkan oleh Pelaku Usaha Toko Online di facebook - I Putu Yogi Saputra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2022)
E-commerce is an activity of buying and selling through internet media. The existence of legal protection for consumers in buying and selling transactions electronically is very important as a guarantee between business actors and consumers in transactions on digital platforms, especially the Facebook marketplace. This study aims to examine the regulation of online buying and selling transactions and examine the legal protection for consumers due to losses in online buying and selling transactions on Facebook. This study was designed using a normative legal research method with a statutory approach. There are two sources of data used, namely primary and secondary data. The data is obtained through the technique of inventorying or tracing legal materials and then classified, documented, recorded, quoted with a qualitative approach. The results show that e-commerce buying and selling transactions are generally regulated in Law Number 11 of 2008 concerning amendments to Law Number 19 of 2016 concerning Information and Electronic Transactions or abbreviated as ITE, especially Article 28 paragraph (1) of the ITE Law. , and Law No. 8/1999 on consumer protection. In legal protection for consumers due to losses in online buying and selling transactions on Facebook, it can be categorized into two, namely preventive and repressive legal protection. Preventive legal protection is legal protection for the community which aims to prevent problems or disputes from occurring. Meanwhile, repressive legal protection is a form of legal protection which is more aimed at resolving disputes